(untitled) (Tidsskrift for Praktisk Teologi, 2019)
Recruitment for employment in the Church of Norway is a matter of concern at the highest level of church leadership. This article looks at pastors’ reflection on their interaction with youth regarding recruitment to theological training and service in the church. Three parish pastors and one youth pastor was interviewed. Schatzkis timespace activity approach has been applied to understand what constitutes pastors’ interaction with youth with recruitment in mind. Spaces that have the potential to open for conversations about a pursuit of career in church are homes and camps where there is more relaxing spare time. However, parish pastors barely interact with youth besides confirmation classes. Therefore, they are prevented from establishing the relationships necessary for talking about a future in the church. The pastors in this study are not particularly engaged in recruitment issues in their everyday work in the local church.